Menakar Pengaturan Tentang Ibu Kota Nusantara Melalui Pasal 18 UUD 1945 - Rizka Marteen, Febbiola (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Law Number 3 of 2022 concerning the National Capital (hereinafter referred to as the “National Capital Law") is the beginning of problems related to the administration of the National Capital of the Republic of Indonesia. This research aims to assess the suitability of the National Capital Law arrangements with the provisions regarding local government in the 1945 Constitution and the factors that cause the form, structure, and arrangements regarding the organizers of the national capital. The mechanism for the formation of the National Capital Law through fast-track legislation is suspected to be the mastermind of the problem of the unconstitutionality of the National Capital Law which resulted in the rejection of the idea of relocating the national capital by the community. This research is conducted by means of a literature study in which the source of research data is obtained from the library. This study includes research on books and laws and regulations related to the national capital which will be discussed descriptively analytically. This research will look for an ideal reconstruction concept of the position of the national capital in the Indonesian constitutional constellation.